Pattern of Refractive Status in Patients with Vernal Keratoconjunctivitis at Birat Medical College Teaching Hospital - Chaudhary, Neha Priyadarshani; Badhu, Badri Prasad; Dev, Barun; Deo, Prabhat (Journal of Nepalgunj Medical College, 2022)
Introduction: Refractive errors remain the most important cause of visual impairment in childhood worldwide which contributes to about 19% of total blindness in the world. This can be further complicated by other ocular conditions like vernal keratoconjunctivitis, which is a chronic, recurrent bilateral inflammation of conjunctiva and cornea.Aims: To assess the pattern of refractive status in patients with Vernal keratoconjunctivitis.Methods: This was a cross sectional hospital-based study conducted in patients attending the Outpatient department of ophthalmology at Birat Medical college Teaching Hospital with the clinical diagnosis of Vernal Keratoconjuctivitis from July 2020 to June 2021.The vision and  baseline refractive status of all patients were assessed accordingly. All the data was recorded in a specifically designed proforma which was then entered in MS excel for statistical analysis.Results: 80 patients were included in the study out of which 85% were male and 15 % were female. The most common presenting age group was 7 to 12 years. The most common type of Vernal Keratoconjunctivitis was found to be mixed type (58%), followed by limbal (22%) and papillary (20%). The most prevalent refractive error was found to be astigmatism (37.5%) followed by hypermetropia (16.25%) and myopia (11.25%). The remaining patients (35%)had a normal state of refraction.Conclusion: Refractive error was commonly seen in patients with Vernal Keratoconjuctivitis in our study. Hence, awareness among the people about the disease is very important.